Mineralogy and chemistry of amphiboles and thermobarometry of Papikion Mt pluton, Rhodope, Northern Greece. - Drakoulis, A.; Koroneos, A.; Soldatos, T.; Papadopoulou, L. (Bulletin of the Geological Society of Greece, 2013)
Papikion Mt pluton which intrudes Kardamos Dome, consists of biotite (Bi), hornblende (Hbl) and biotite-hornblende (Bi-Hbl) bearing rock types. In this work the relationship among the amphiboles of each Hbl-bearing rock type is studied. Moreover, their minimum crystallization pressure and temperature are estimated. The amphiboles of the Hbl granodiorite (GRD), the Bi-Hbl diorite (DR) and the Hbl diorite (DR) are classified mainly as magnesiohornblende and ferrohornblende and the amphiboles of the Bi-Hbl GRD as ferroedenite and hanstingsite. It is to note that some samples contain amphibole crystals showing a sieved texture with quartz. These sieved amphiboles have no chemical differences from the rest amphibole crystals. This texture can probably derive from the breakdown of mafic minerals of an assimilated xenolith such as pyroxenes and hornblende itself, leaving quartz. Using the Al-in-hornblende geobarometer and the plagioclase-hornblende geothermometer), minimum crystallization pressures from 4.6 to 5.2 kbar and temperatures from 700 to 740 °C were estimated for the Bi-Hbl GRD. The DR shows crystallization pressures ranging from 6.4 to 7.4 kbar and temperatures ranging from 620 to 700 °C. The Hbl GRD shows the lowest P-T values, thus an average crystallization pressure about 3 kbar and an average temperature about 600 °C were estimated.